Learning Design Based on Technology in Islamic Education - Hasanah, Rodiatul; Lestari, Elok Puji; Fausiyah, Fausiyah; Fawait, Agus (PT. Riset Press International, 2025)
Study aims to describe the design of technology-based learning in Islamic education. This is because, in the current digitalization era, we cannot be separated from technological advances in designing learning in Islamic educational institutions. This study uses a qualitative approach with a library research method by collecting information. from various journals and books. The results of the analysis show that progress knowledge obligatory environment education including Islamic education For Keep going adapt with development technology. One of the effective model is the ADDIE approach that has an impact positive in increase quality learning and helping student reach potential maximum they based on characteristics, quality as well as ability participant educate.